Core stories of physicians on a Swiss internal medicine ward during the first COVID-19 wave: a qualitative exploration (Swiss Medical Weekly, 2024)
INTRODUCTION: The first COVID-19 wave (2020), W1, will remain extraordinary due to its novelty and the uncertainty on how to handle the pandemic. To understand what physicians went through, we collected narratives of frontline physicians working in a Swiss university hospital during W1.METHODS: Physicians in the Division of Internal Medicine of Lausanne University Hospital (CHUV) were invited to send anonymous narratives to an online platform, between 28 April and 30 June 2020. The analysed material consisted of 13 written texts and one audio record. They were examined by means of a narrative analysis based on a holistic content approach, attempting to identify narrative highlights, referred to as foci, in the texts.RESULTS: Five main foci were identified: danger and threats, acquisition of knowledge and practices, adaptation to a changing context, commitment to the profession, and sense of belonging to the medical staff. In physicians’ narratives, danger designated a variety of rather negative feelings and emotions, whereas threats were experienced as being dangerous for others, but also for oneself. The acquisition of knowledge and practices focus referred to the different types of acquisition that took place during W1. The narratives that focused on adaptation reflected how physicians coped with W1 and private or professional upheavals. COVID-19 W1 contributed to revealing a natural commitment (or not) of physicians towards the profession and patients, accompanied by the concern of offering the best possible care to all. Lastly, sense of belonging referred to the team and its reconfiguration during W1.CONCLUSIONS: Our study deepens the understanding of how physicians experienced the pandemic both in their professional and personal settings. It offers insights into how they prepared and reacted to a pandemic. The foci reflect topics that are inherent to a physician’s profession, whatever the context. During a pandemic, these foundational elements are particularly challenged. Strikingly, these topics are not studied in medical school, thus raising the general question of how students are prepared for the medical profession.